Peran Dinas Sosial Dalam Menanggulangi Gelandangan Dan Pengemis Di Kota Tanjungpinang - Qorina Salsabila; Gabriela Purba; Selvia Evayanti Saragih (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2022)
Homeless and beggars are the result of social problems that cannot be avoided. This social problem is the interaction and accumulation of various problems such as poverty, low education, lack of work skills, socio-cultural environment, health, and so on. Department of Social Affairs as the agency responsible for social problems whether it has been maximized or not. The method used in this study uses qualitative methods with data collection techniques taken from the publications of the Tanjung Pinang city government itself. From the results obtained, there are still many homeless people and beggars, there are even increasing groups. Actually the plans made by the Social Service are good, from the vision, mission, goals, objectives, strategies, and programs. However, in reality, the performance has not been maximized and has not even been realized at all. For example, rehabilitation facilities and infrastructure in the city of Tanjung Pinang still do not exist.